2004
DOI: 10.1177/002215540405200205
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of M-Cadherin-stained Satellite Cells Declines in Human Muscles During Aging

Abstract: To answer the question of whether the satellite cell pool in human muscle is reduced during aging, we detected satellite cells in 30- microm-thick transverse sections under the confocal microscope by binding of M-cadherin antibody. The basal lamina was detected with laminin. Nuclei were stained with bisbenzimide or propidium iodide. Satellite cells were counted by applying the disector method and unbiased sampling design. To determine if there are age-related differences in muscle fiber types, morphometric cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
71
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(73 citation statements)
references
References 44 publications
1
71
1
Order By: Relevance
“…Our studies demonstrate that M-CAM is expressed on human fetal myogenic cells and its downregulation appears necessary to promote cell fusion. On cytospins of cultured cells, M-CAM was co-expressed with the myoblast-specific markers desmin and M-cadherin, whereas on tissue sections M-CAM colocalized with cells positive for the myogenic markers Pax7 (Seale et al, 2000;Olguin and Olwin, 2004;Zammit et al, 2004) and M-cadherin (Irintchev et al, 1994;Sajko et al, 2004). Collectively, these results suggested that M-CAM may be a novel marker for activated satellite cells, because it appears to be expressed by cells weakly positive for Pax7 (Zammit et al, 2004) and on cultured satellite cells expressing desmin and M-cadherin (Cornelison and Wold, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Our studies demonstrate that M-CAM is expressed on human fetal myogenic cells and its downregulation appears necessary to promote cell fusion. On cytospins of cultured cells, M-CAM was co-expressed with the myoblast-specific markers desmin and M-cadherin, whereas on tissue sections M-CAM colocalized with cells positive for the myogenic markers Pax7 (Seale et al, 2000;Olguin and Olwin, 2004;Zammit et al, 2004) and M-cadherin (Irintchev et al, 1994;Sajko et al, 2004). Collectively, these results suggested that M-CAM may be a novel marker for activated satellite cells, because it appears to be expressed by cells weakly positive for Pax7 (Zammit et al, 2004) and on cultured satellite cells expressing desmin and M-cadherin (Cornelison and Wold, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Actually, the number of satellite cells declines with age in humans. 16,17 In addition, the proliferation potential of human muscle satellite cells is limited by cellular senescence induced by progressive telomere shortening. 16,18 When the telomere length becomes less than about 5 kb, the Rb and p53 pathways are activated and culminate in irreversible growth arrest.…”
Section: Discussionmentioning
confidence: 99%
“…The correlation with the cross-sectional fiber area allows processes like muscle growth, pathological events, and ageing to be taken into account (Sajko et al 2004), but it has been suggested that ideally both satellite cells per fiber and satellite cells per number of myonuclei should be used together for a more accurate measurement (Lindstrom and Thornell 2009). …”
Section: Quantification Of Human Satellite Cellsmentioning
confidence: 99%